2017
DOI: 10.1186/s11671-017-2267-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polyethylene Glycol on the NiO Photocathode

Abstract: In this study, a uniform nanoporous NiO film, with a thickness of up to 2.6 μm, was prepared using polyethylene glycol (PEG). The addition of PEG significantly decreased the cracks in the NiO film and prevented the peeling of the NiO film from a fluorine-doped tin oxide substrate. The NiO cathode was prepared using CdSeS quantum dots (QDs) as the sensitizer, with an optimized photoelectric conversion of 0.80%. The optimized QD-sensitized NiO films were first assembled with the TiO2 anode to prepared QD-sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…( Zhang Q. et al, 2016 ; Kuang et al, 2016 ; Wang Z. et al, 2020 )The combination of the OER catalyst and the semiconductor light absorber can not only improve the PEC activity by providing an interface reaction active site that reduces overpotential, but also improve the PEC stability by rapidly consuming photo-generated carriers of semiconductor materials against electrolytes ( Zhou et al, 2015 ). ( Trotochaud et al, 2014 ; Zeng et al, 2021b ) Recently, Dai ( Kenney et al, 2013 ; Li et al, 2017 ) and colleagues deposited an ultra-thin nickel film on the n-type silicon substrate as a physical protective layer. It was found that a 2 nm nickel film played a crucial role in the sustainability of n-type silicon photoanodes in the solar-driven water oxidation process.…”
Section: Introductionmentioning
confidence: 99%
“…( Zhang Q. et al, 2016 ; Kuang et al, 2016 ; Wang Z. et al, 2020 )The combination of the OER catalyst and the semiconductor light absorber can not only improve the PEC activity by providing an interface reaction active site that reduces overpotential, but also improve the PEC stability by rapidly consuming photo-generated carriers of semiconductor materials against electrolytes ( Zhou et al, 2015 ). ( Trotochaud et al, 2014 ; Zeng et al, 2021b ) Recently, Dai ( Kenney et al, 2013 ; Li et al, 2017 ) and colleagues deposited an ultra-thin nickel film on the n-type silicon substrate as a physical protective layer. It was found that a 2 nm nickel film played a crucial role in the sustainability of n-type silicon photoanodes in the solar-driven water oxidation process.…”
Section: Introductionmentioning
confidence: 99%